Systematic Literature Review of Near Field Communication Technology Acceptance for Daily Life Appliance - Al Ghozali, Isnen Hadi; Akbar, Ipal; Handoko, Andy Rio (Jurnal Ilmiah FIFO, 2024)
In the era of Internet of Things (IoT) development, there are many technologies that support the digital ecosystem, one of which is Near Field Communication (NFC). The basic standards for NFC devices have been developed since 2004. However, the practical and academic use of NFC is still limited. To address these issues, many researchers propose prototypes and the use of NFC. As a result, this study was designed to delve deeper into the findings of NFC-themed research. This study uses a systematic literature review method. This study aims to classify and examine the latest topics from various research results with the theme of NFC, which are classified into eight areas of use for the period 2018–2022. The results of this study found 9 articles (15.8%) related to medical appliances, 12 articles (21.1%) related to security issues, 9 articles (15.8%) related to education appliances, 7 articles (12.3%) related to mobile payments, 6 articles (10.5%) related to communication appliances, 7 articles (12.3%) related to business administration, 4 articles (7.0%) related to tourism support, and 3 articles (5.3%) related to infrastructure appliances. This finding can be a trigger for further researchers to raise the theme of NFC related to infrastructure appliances.